North and South Meet through Computer Collaboration: A Learning Experience for Preservice Teachers - Marion Harris Fey; Mary Ann Tighe (Networks: An Online Journal for Teacher Research, 1999)
North and South Meet through Computer Collaboration: A Learning Experience for Preservice Teachers